Writing Russia - Dowling, Melissa-Ellen, 1990- author.
1 online resource.
Keywords: "Writing Russia offers the first systematic analysis of Anglophone national histories of Russia. By deconstructing preeminent historical works on the history of Russia, this book provides insight into the hidden ideological underpinnings of the texts and their representations of Russia in the West. It demonstrates that historians employ a range of literary techniques to smooth over contradictions in their narratives of Russia, generating a seemingly cohesive depiction of Russia as a liminal, Other nation. This is a process that this book theorises as "discordus", representing an original conceptual framework for examining national history texts. It identifies patterns in the language and emplotment of Anglophone Russian histories across several defining historical epochs from the Mongol conquests to the Putin presidency, revealing the extent to which historians wield the narrative power to "make or break" nations. Postmodern in approach, the work pushes the boundaries of historiography and calls into question the nature of history"--